The role of the administrative account and problems of its introduction - Довжик, О. О. (Scientific Progress & Innovations, 2012)
The role of the administrative account in a control system of the enterprise is analyzed. It determines that management accounting is an effective management instrument as it creates a competitive advantage in the market. The basic principles of construction of system of the administrative account at the enterprise of a modern type are selected. And its importance for maintenance of effective functioning. The main problems preventing the implementation of management accounting are analyzed in the article. And the activities for successful implementation of this process in the Ukrainian enterprises are determined here.